2020
DOI: 10.1093/ecco-jcc/jjaa185
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Receptor of SARS-CoV-2 in Inflamed IBD Tissue Seems Downregulated by HNF4A in Ileum and Upregulated by Interferon Regulating Factors in Colon

Abstract: Background Patients with IBD are considered immunosuppressed, but do not seem more vulnerable for COVID-19. Nevertheless, intestinal inflammation has shown an important risk factor for SARS-CoV-2 infection and prognosis. Therefore, we investigated the role of intestinal inflammation on the viral intestinal entry mechanisms, including ACE2, in IBD. Methods We collected inflamed and uninflamed mucosal biopsies from CD (n=193) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 64 publications
6
40
0
1
Order By: Relevance
“…The two recent landmark studies ( 6 , 7 ) have confirmed that SARS-CoV-2 could productively infect human gut enterocytes and intestinal organoids. In our study, we found that IBD patients had a higher expression of ACE2 in colon tissue while lower in ileum tissue vs. healthy control, which was consistent with the published data ( 13 ). Additionally, our result showed that the expression of colonic epithelial ACE2 was downregulated in IBD patients responding to anti-TNFα therapy, using GEO data analysis and then validated with qPCR and IHC assays.…”
Section: Discussionsupporting
confidence: 93%
“…The two recent landmark studies ( 6 , 7 ) have confirmed that SARS-CoV-2 could productively infect human gut enterocytes and intestinal organoids. In our study, we found that IBD patients had a higher expression of ACE2 in colon tissue while lower in ileum tissue vs. healthy control, which was consistent with the published data ( 13 ). Additionally, our result showed that the expression of colonic epithelial ACE2 was downregulated in IBD patients responding to anti-TNFα therapy, using GEO data analysis and then validated with qPCR and IHC assays.…”
Section: Discussionsupporting
confidence: 93%
“…25 Other studies involving human intestinal organoid experiments confirmed the mechanism of viral entry into intestinal cells, as well as the molecular expression pattern associated with the viral invasion in a context of intestinal inflammation (patients with inflammatory bowel diseases). 26,27 Differences in the expression of molecules related to viral entry depended on the analyzed intestinal segment, ileum or colon. 27 In the present study, the treatment with a mixture of acetate, propionate, and butyrate did not alter the viral load of intestinal biopsies or intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in contrast to worse outcomes in ACE2-high colon expressing adults, reduced ileal ACE2 expression in CD patients (N=50) in the Pediatric RISK Stratification cohort was significantly associated with colon and ileum disease involvement (p=0.0014), deeper ileal ulcers (p=0.0002), and macroscopic ileal inflammation (p=0.0156) compared to pediatric ileal ACE2-high (N=50) patients. These regional differences in ACE2 expression suggest that active intestinal inflammation alters ACE2 expression, with opposing regulation in ileum and colon 17, 18 . There are several points that must be noted with regard to future comparison of our findings with other studies.…”
Section: Discussionmentioning
confidence: 99%